Anthropological analysis of neolithic and Early Bronze Age skeletons-a classical and molecular approach (East Slavonia, Croatia) - Hincak, Zdravka (Array, 2007)
Theories about the first Indo-European migration are numerous. Significant contribution in attempt to resolve these theories is given by analysing skeletal material from two biggest prehistoric archaeological sites from N-E Croatia. Eight skeletons of Starcevo culture from sites "Nama" and "Hotel" at Vinkovci (6100-5500 BC) and seven skeletons of Vucedol culture from the site Vineyard Streim at Vucedol near Vukovar (3000-2500 BC) were analysed. Methods of classical anthropological analysis tried to distinguish the differences among members of both populations, while the methods of molecular genetics were used in defining possible genetic structure of both ancient populations. Established differences speak on the behalf of the theory of Maria Gimbutas about the first Indo-European migration with a cattle breeding population from the east around 3500 BC.